Impact of Hashimotoas thyroiditis on clinicopathologic features of papillary thyroid carcinoma associated with infiltration of tumor-infiltrating lymphocytes - Wang, Lin (Int J Clin Exp Pathol, 2018)
The association between Hashimoto’s thyroiditis (HT) and papillary thyroid carcinoma (PTC) has been a long and ongoing controversy. In the present study, a total number of 322 patients who underwent thyroidectomies were retrospectively studied, and the impact of HT with the incidence, clinicopathologic features, and presence of CD4+, CD8+ tumor-infiltrating lymphocytes (TILs) in PTC patients were analyzed. We further explored the correlation between CD4+, CD8+ TILs and clinicopathologic features in PTC patients with and without HT. The incidence of HT concurrent with PTC was 42.9%, which was significantly associated with a younger age (P=0.039) and the presence of hyperthyroid (P=0.010). The PTC patients coexistent with HT tended to be more female (P=0.001), with diffuse swelling of the thyroid (P<0.001), decreased TSH (P=0.004), and elevated anti-TgAb (P<0.001) and anti-TPOAb (P<0.001). The tumor size of PTC with HT was smaller (P=0.006) and exhibited more bilateral tumors (P<0.001) and less lymph node metastasis (P=0.016). Furthermore, CD4+ and CD8+ TILs in PTC with HT were significantly higher than without HT (both P<0.001). Both high CD4+ and CD8+ TILs were significantly associated with elevated TSH (P=0.019 and P=0.023, respectively), anti-TgAb (P=0.002 and P=0.001, respectively) and anti-TPOAb (P=0.001 and P=0.003, respectively), and the tumor size was smaller (P=0.017 and P=0.039, respectively) and with less lymph node metastasis (P=0.012 and P<0.001, respectively) in PTC with HT. Our study suggests that HT is significantly associated with PTC, which might be ascribed to infiltration of CD4+, CD8+ TILs.